Smart Dust Detection and Automated Cleaning for Photovoltaic Systems in Hydroponic Farming Applications - Sy Yi, Sim; Mohamad Rafie, Muhammad Aiman; Azman, Muhammad Aliff Hafeez; Hasan Mousay, Khalid Aboubakr; Lim Meng Siang, Alvin John; Azri, Muhamad Azfar; Mat Yusoh, Mohd Abdul Talib (Multidisciplinary Applied Research and Innovation, 2025)
The efficient operation of photovoltaic (PV) systems is significantly impacted by dust accumulation on solar panels, which can reduce power output. To combat this, a smart dust detection and automated cleaning system has been developed, utilizing low-cost dust sensors placed across the PV array to monitor dust levels continuously. The data is transmitted to a central control unit that employs advanced algorithms to determine optimal cleaning schedules based on predefined cleanliness thresholds. When significant dust accumulation is detected, the system activates an automated cleaning mechanism involving an ESP32 microcontroller, DC motors, a water pump, and a motor driver. This approach has demonstrated a notable improvement in voltage output and reduced energy losses while minimizing manual maintenance efforts. Overall, the system enhances the efficiency and performance of PV installations, contributing to their sustainability and longevity by optimizing energy generation and reducing downtime and maintenance costs.